Atomically dispersed Fe in a C2N Based Catalyst as a Sulfur Host for Efficient Lithium–Sulfur Batteries. Issue 5 (18th December 2020) - Liang, Zhifu; Yang, Dawei; Tang, Pengyi; Zhang, Chaoqi; Jacas Biendicho, Jordi; Zhang, Yi; Llorca, Jordi; Wang, Xiang; Li, Junshan; Heggen, Marc; David, Jeremy; Dunin‐Borkowski, Rafal E.; et al.
Abstract: Lithium–sulfur batteries (LSBs) are considered to be one of the most promising next generation energy storage systems due to their high energy density and low material cost. However, there are still some challenges for the commercialization of LSBs, such as the sluggish redox reaction kinetics and the shuttle effect of lithium polysulfides (LiPS). Here a 2D layered organic material, C2 N, loaded with atomically dispersed iron as an effective sulfur host in LSBs is reported. X‐ray absorption fine spectroscopy and density functional theory calculations prove the structure of the atomically dispersed Fe/C2 N catalyst. As a result, Fe/C2 N‐based cathodes demonstrate significantly improved rate performance and long‐term cycling stability. Fe/C2 N‐based cathodes display initial capacities up to 1540 mAh g −1 at 0.1 C and 678.7 mAh g −1 at 5 C, while retaining 496.5 mAh g −1 after 2600 cycles at 3 C with a decay rate as low as 0.013% per cycle. Even at a high sulfur loading of 3 mg cm −2, they deliver remarkable specific capacity retention of 587 mAh g −1 after 500 cycles at 1 C. This work provides a rational structural design strategy for the development of high‐performance cathodes based on atomically dispersed catalysts for LSBs. Abstract : A novel atomically dispersed catalyst prepared by loading iron atoms into a 2D organic layered material (C2 N) is shown. C2 N has abundant holes and pyrazine nitrogen in its structure. The Fe2 N6 coordination structure is shown to work as an efficient active site in the cathode of lithium–sulfur batteries for promoting reversible electrochemical conversion during charging and discharging.